Effects of Credit Memos on Performance Accountant on Uncollectible Receivables - Aini, Qurotul; Simbolon, Rosdiana; Dewi, Shylvia Ratna (Pandawan, 2019)
In the current era we have entered the disruptive 4.0 era where sophistication has been applied in the finance of a company to record every expense incurred by an institution or company. In the transaction process as it is now does not rule out the possibility of several triggers for making a deposit such as the example of a sales or purchase return and overpayment if it is not handled immediately it will arise as a financial report problem. The Cloud Accounting system is equipped with a credit memo facility which is divided into 2 (two) parts, namely customer memo credit and supplier memo credit. The Cloud Accounting system is then equipped with a credit memo facility which is divided into 2 (two) parts, namely customer memo credit and supplier memo credit. Where customer memo credit is the customer entrusting a sum of money to the company, it will be used as a payment on the upcoming sales bill. While supplier memo credit is the balance that arises due to overpayment, then the deposit will be used as a discount on future sales bills. By using a memo credit based on Cloud Accounting, it can minimize crime or crime at the company because it has been certified by ISO / IEC 2700.